Effects of Organic Amendments on the Transformation of Fe (Oxyhydr)Oxides and Soil Organic Carbon Storage - Wen, Yongli; Xiao, Jian; Goodman, Bernard A.; He, Xinhua (Frontiers in Earth Science, 2019)
Organic amendments from animal production are commonly used for promoting soil fertility, and their impacts on the residual soil organic carbon (SOC) are of both agricultural and environmental interest. Iron (Fe) in the form of (oxyhydr)oxides has been proposed to play a critical role in long-term SOC preservation by forming Fe-organic associations, though currently a comprehensive understanding of how these Fe-organic associations are regulated by long-term organic amendments is limited. Here, we synthesize information to link Fe (oxyhydr)oxides, SOC sequestration, and long-term organic inputs from both field and laboratory studies. The results show that vigorous Fe mobilization can be regulated by long-term application of organic amendments, and these organically amended soils contained significantly higher concentrations of poorly crystalline Fe that was closely related to SOC storage in both upland and paddy soils. Potential mechanisms are proposed as follows: (1) DOM from the organically-amended soils is more likely to co-precipitate with poorly crystalline Fe, and DOM from the inorganically-fertilized soils is to a larger extent adsorbed on poorly crystalline Fe. The co-precipitated Fe-OM complexes are more resistant to desorption than the adsorbed OM. (2) DOM extracts from soils treated with organic amendments exhibit a stronger inhibitory effect on the crystallization of poorly crystalline Fe than DOM from inorganically fertilized soils, which may be the consequence of increased numbers of aromatic functional groups. Organic acids in root exudates increased soil mineral availability and the formation of poorly crystalline minerals. Compared to inorganic fertilizers, organic amendments significantly increase (> 20%, p < 0.05) the concentration of poorly crystalline minerals in the presence of actual roots. (3) Microbially-mediated Fe cycling is strongly linked to the Fe mineralogy in soils, and regulated by long-term organic amendments. Greater consumption of poorly crystalline Fe was observed in inorganically-fertilized soil than that in organically amended soil, due to a higher relative abundance of Fe(III) reducers. Conversely, Fe(II) oxidizers were more abundant, and produced higher levels of poorly crystalline Fe under organic amendments. In conclusion, continuous organic amendments initialize a positive feedback loop for the maintenance of poorly crystalline Fe in soils, which can contribute to enhanced SOC storage.